Yield Grade and Quality Assessment of Native Buffalo Meat and Beef at Different Ages - B. K. Roy; N. Huda; K. S. Huque; N. Sultana; N. R. Sarker (Faculty of Animal Science, Bogor Agricultural University, 2020)
Boosting meat production potential possibly happens when people will judge meat quality and use their livestock wisely, as they meet up their demand from promising animal like buffalo. To evaluate the productive performances and quality assessments of beef and buffalo meats, cattle (Pabna) and buffalo (Native, swamp type) were fattened for 120 days with a single plane of nutrition in a 2×3 (Species×Age) factorial experiment. By slaughtering, the carcass and non-carcass characteristics, primal cuts, pH, drip loss, cooking loss, color, intramuscular fat of meat, marbling score, and yield grade of meat were determined through univariate GLM procedure based CRD analysis. Live and carcass weights of buffalo were significantly higher (p<0.001), but the dressing percentage was significantly lower (p<0.001) than cattle (52.1% & 55.3%, respectively). Species variation and age have a great impact on the yield of primal cuts. Meat: bone of cattle (5.33:1.00) was significantly better (p<0.001) than buffalo (4.57:1.00). Buffalo meat was darker and reddish (p<0.01) in color, and with the increment of age, it was increased (p<0.001). A little amount (p<0.001) of intramuscular fat was found in buffalo meat (0.44%) than cattle (3.31%). The marbling score was measured higher (p<0.001) in cattle than buffalo (5.00 and 3.85, respectively). Buffalo meat scored 3 in 5 scale yield grade point where beef gained 3.5 scores and showed a significant (p<0.05) difference. Finally, buffalo meat scored better than beef with the measures of yield grade, marbling score, and fat percentage, though its lower carcass yield and demerits of a reddish color.